MODEL FILANTROPI ISLAM: PROGRAM RUMAH MAKAN GRATIS BERBASIS SEDEKAH DAN IMPLIKASINYA TERHADAP KETAHANAN PANGAN MASYARAKAT - Ahmad Saiful Anam; Almaika Nur Elisza; Athalia Devi Apita Sari; Mahardika Cipta Raharja (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Food insecurity among certain communities shows that access to food remains unequal to all levels of society, particularly those in the lower economic classes. In this context, the alms-based free lunch program presents itself as an innovative form of Islamic philanthropy that relies on the participation of individual donors. This study aims to examine the application of individual Islamic philanthropy in the management of the free meal program and to examine its contribution to strengthening community food security. The research was conducted using a descriptive qualitative approach through field studies using data collection techniques such as interviews, observation, and documentation. The results indicate that the alms funds collected voluntarily from the community are systematically managed to support the provision of ready-to-eat meals for beneficiaries on a regular basis. The program has been proven to help expand community access to food, reduce household expenses, and strengthen social awareness and a spirit of sharing within the community. However, the program's sustainability is greatly influenced by the continuity of donor contributions and the quality of institutional management